Gastric Ulcer Bleeding Caused by Systemic Inflammatory Response to Mycobacterial Bacteremia - Soo Bin Synn; Su Jin Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Adipose-derived stem cells are gaining attention because they are easily obtained in large quantities. However, concerns about side effects of their use have also been raised. Mycobacterial infections can develop during stem cell treatment in the event of incomplete medical device sterilization and/or suboptimal hygiene during cell processing and culture. In general, mycobacterial infections most frequently manifest as pneumonia; however, infections of the bones, lymph nodes, skin, soft tissues, and blood also occur. Mycobacterial bacteremia occurs relatively frequently, but cases of gastric ulcers induced as a complication of stem cell treatment and subsequent mycobacterial bacteremia have not been reported. Herein, we report a 75-year-old man who developed mycobacterial bacteremia and gastric ulcers following adipose-derived stem cell injection. This case report raises awareness of the possibility of Mycobacterium abscessus complex bacteremia and subsequent gastric ulcer bleeding—a rare complication of stem cell therapy.